The importance of proper and prompt treatment of ocular syphilis: a lesson from permanent vision loss in 52 eyes. (25th June 2020) - Gu, X.; Gao, Y.; Yan, Y.; Marks, M.; Zhu, L.; Lu, H.; Guan, Z.; Shi, M.; Ni, L.; Peng, R.; Zhao, W.; Wu, J.; et al.
Abstract: Background: Ocular involvement can occur at any stage of syphilis. Prompt diagnosis and proper treatment of ocular syphilis are vital to avoid long‐term consequences. Objectives: To describe the risk factors for ocular syphilis and clinical features of blindness caused by syphilis. Methods: We report risk factors for ocular syphilis amongst patients seen at the Shanghai Skin Disease Hospital between October 2009 and October 2017. We identify patients with ocular syphilis resulting in blindness and report the clinical characteristics, laboratory findings and treatment outcomes of these patients. Results: A total of 8310 new cases of syphilis were seen, of which 213 patients had ocular disease and 50 patients had blindness due to syphilis. Increasing age and higher RPR titres were associated with ocular involvement but there was no association with HIV status. Blindness in syphilis was restricted predominantly to patients with optic nerve involvement and not patients with isolated uveitis. Fifty patients (and a total of 67 eyes) met the WHO definition of blindness prior to treatment for syphilis. At the end of follow‐up, vision had improved in 24 of 67 eyes (35.8%) after treatment. Successful treatment of uveitis was associated with the best improvement in visual acuity, whilst patient with underlying optic atrophy prior to treatment had the worst visual outcome. Conclusions: Ocular involvement is an important manifestation of syphilis which may result in blindness. Our data demonstrate outcomes for ocular syphilis are poor if detected late; early recognition and diagnosis is therefore vital to avoid permanent visual loss.